2019
DOI: 10.2196/12041
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Doctors’ Usage Paths of Mobile Electronic Health Records Across Specialties: Comprehensive Analysis of Log Data

Abstract: BackgroundWith the emergence of mobile devices, mobile electronic health record (mEHR) systems have been utilized by health care professionals (HCPs), including doctors, nurses, and other practitioners, to improve efficiency at the point of care. Although several studies on mEHR systems were conducted, including those analyzing their effects and HCPs’ usage frequency, only a few considered the specific workflows of doctors based on their specialties in which the work process differs greatly.ObjectiveThis study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In this study, we also used detailed EHR and inbox usage characteristics such as window switching, inbox work batching, the time per message, message types, and the time distribution between work and nonwork hours. Our finding that the window switching rate was positively associated with stress could reflect the complexity and repetitiveness of physicians’ EHR interactions, as indicated in prior work [ 56 ], and the efficiency issues often associated with physicians’ satisfaction with EHRs [ 57 ]. Another study on EHR inbox burden [ 8 ] also reported that excessive steps were needed to process messages and that physicians recommended reducing the number of mouse clicks necessary to process messages.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In this study, we also used detailed EHR and inbox usage characteristics such as window switching, inbox work batching, the time per message, message types, and the time distribution between work and nonwork hours. Our finding that the window switching rate was positively associated with stress could reflect the complexity and repetitiveness of physicians’ EHR interactions, as indicated in prior work [ 56 ], and the efficiency issues often associated with physicians’ satisfaction with EHRs [ 57 ]. Another study on EHR inbox burden [ 8 ] also reported that excessive steps were needed to process messages and that physicians recommended reducing the number of mouse clicks necessary to process messages.…”
Section: Discussionmentioning
confidence: 55%
“…Most studies use basic measures to characterize EHR usage, such as the duration of time [ 14 , 15 , 55 ]. In one study, researchers used more complex measures to characterize mobile EHR usage, such as the number of log-ins and features used and usage paths (ie, the frequency and complexity of consecutive actions) [ 56 ]. They compared doctors across medical specialties and found that physicians other than surgeons had more diverse mobile EHR usage patterns with higher complexity and repetitive loops compared to surgeons [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The users are classified according to benchmarks or threshold set for each group and App, which varies between research studies. Lastly, the user groups can be identified by categorizing or clustering users according to their: demographics, such as their age or gender [37,45]; their occupations or specialties [29,36,46]; or their device specifications such as the operating system [38], mobile platforms [37] or network [36]. User groups are identified and can be used to generate specific insights per user group.…”
Section: Inactive Usage [30] Lost Usersmentioning
confidence: 99%
“…According to the hazard ratio (HR) values after the multivariate Cox regression analysis, we classified the m6A-related prognostic AS events into protective/risky AS events (HR > 1 as a risk factor; HR < 1 as a protective factor), and showed the Sankey diagram that plotted is by "ggalluvial, dplyr, and ggplot2" R packages (Graedel, 2019;Soh et al, 2019). According to the median value of the risk score of the signature of each cohort, we divided the LUAD and LUSC cohorts into two subgroups, that is, the high-and low-risk groups.…”
Section: Risk Model Constructionmentioning
confidence: 99%